ASAS â€œDAPAT DILAKSANAKANâ€ DALAM PERATURAN PERPAJAKAN - Rinaningsih (Scientax, 2020)
Tax revenues paid by taxpayers are the main source of state revenue at this time. Individual and corporate taxpayers owed tax in Indonesia are spread throughout the territory of Indonesia. However based on the data, the tax ratio of each province is vary. Therefore, in this paper we will discuss whether the existing tax regulations are in accordance with the existing conditions.This study uses a qualitative descriptive method. Based on the research, due to the principle "can be implemented" in the Law of the Republic of Indonesia Number 12 of 2011, several current tax regulations have been formulated without considering existing conditions namely the geographical conditions of various tax officesâ€™s work areas, the uneven availability of the internet in each region along with the unsupported behavior of internet users for electronic services, and unavailability of the postal services in some villages. Those make taxation regulations difficult to be implemented in all regions of Indonesia and do not support the optimum collection of taxes in all regions of Indonesia. The aim of the research is to provide recommendations to the DGT to improve the tax regulations to a better level.